Gender and Exercise Habits as Factors Causing Work Stress in Surabaya City Health Office Employees - Alfayad, Afan; Haqi, Dani Nasirul; Alayyannur, Putri Ayuni; Dwiyanti, Endang; Juwono, Kholifah Firsayanti (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Organizational success is influenced by the performance of each employee in it. Work stress experienced by the employees is one of the obstacles in improving the quality of the organization. Another research showed that employees of Manado City Health Office experienced 27.7% low stress and 72.3% moderate stress, which affected the work productivity of the employees. This research aims to see the relationship between gender and exercise habits on the stress experienced by the employees of Surabaya City Health Office. Method: This research is an observational type of research where the primary data were obtained from the responses of 32 employees of the Surabaya City Health Office. The data were collected by using a questionnaire based on the Regulation of the Minister of Manpower No. 5 of 2018 concerning Occupational Health and Safety in the Work Environment. The primary data obtained were then analyzed using cross-tabulation in a data processing software. Result: This research shows that, with an alpha of 5% (0.005), the relationship between gender and work stress events has a significance value of 0.013, while the relationship between exercise habits and work stress events has a significance value of 0.006. Conclusion: This research shows that there is a significant relationship between gender and exercise habits on stress events in Surabaya City Health Office employees. Women employees experience a higher incidence of work stress than male employees. Furthermore, the habit of exercising can reduce stress events because exercising can stimulate endorphins which play a role in creating a sense of calm, reducing pain, and releasing tension